Potensi Industri Produk Plastik Berbasis Industri Rumah Tangga dengan Alat Vacuum Forming Sederhana - Dian Cahyadi; Lanta L (Seminar Nasional LP2M UNM, 2019)
The needs of the home industry (IRT) for plastic packaging for their products are currently higher along with the increasing culinary snacks industry (food / beverage). Awareness of the importance of packaging their products has become a major focus in efforts to increase the selling value of the product. Therefore, many culinary IRTs try to make breakthroughs in presenting the appearance of their products to be different from other similar products. However, the obstacle that was encountered was the limitation of variations in model / package design that could be obtained or used as alternatives. Another obstacle is when they want to place an order based on their own design, it results in a high value that must be redeemed. This is due to the selling price associated with the production limit of production costs which ultimately forces the IRT to incur significant costs. This research was conducted to produce a tool that can be presented with the ability to produce tools that can be done on a local scale, economical product prices, and easy operation.